Psychological implications of coronavirus disease 2019 outbreak in patients with chronic diseases: A systematic review - Farzin Bagheri Sheykhangafshe; Maryam Esmaeilinasab (Chronic Diseases Journal, 2021)
BACKGROUND: During the coronavirus 2019 (Covid-19) pandemic, patients with chronic diseases faced many challenges like greater risk of Covid-19 and delay in treatment which increase the possibility of psychological problems in these individuals. In this regard, the present study was conducted to investigate the psychological consequences of the Covid-19 epidemic in this group of patients.